The Nursery of Juvenile Sandfish, Holothuri scabra in Pen-culture - Tomatala, Pitjont; Madubun, Usman (Jurnal Ilmiah Platax, 2024)
This research aims to be a reference for better and regionally characteristic sandfish nursery activities to support sustainable sea cucumber farming. This research was carried out in the waters of Ohoitel village, Tual City, and took place from March – April 2023. 450 sandfish seeds measuring 0.39 – 1.98 gr were stocked in Pen-culture measuring 4 x 3 x 0.7 meters. Pen culture is made of waring and has a cover. Calculation of survival and growth measurements only at the beginning and end of rearing. Water quality measurements (temperature, salinity, and pH) were carried out every week during the research. Based on the research results, it can be concluded that the nursery of seeds sandfish measuring 0.39 – 1.98 gr can be done in Pen-culture using a cover. This is because the survival percentage of sandfish chicks raised in Pen-culture is 84 - 86.67% with an average survival percentage of 85.33% and a body weight growth range of 2.54 - 12.97 gr with an average of the average absolute growth in body weight was 6.77 gr. Keywords: Nursery, Sandfish, Pen-culture Abstrak Penelitian ini bertujuan menjadi referensi kegiatan pendederan teripang pasir yang lebih baik dan berkarakteristik daerah guna menopang budidaya teripang secara berkelanjutan. Penelitian ini dilaksanakan di perairan desa Ohoitel, Kota Tual dan berlangsung dari Maret 2023 – April 2023. Benih teripang pasir berukuran 0,39 – 1,98 gr sebanyak 450 ekor ditebar pada Pen-culture berukuran 4 x 3 x 0,7 meter. Pen-culture terbuat dari waring dan memiliki penutup. Perhitungan kelangsungan hidup dan pengukuran pertumbuhan hanya pada awal dan akhir pemeliharaan. Pengukuran kualitas air (suhu, salinitas dan pH) dilakukan setiap minggu selama penelitian. Berdasarkan hasil penelitian dapat disimpulkan bahwa pendederan anakan teripang pasir berukuran 0,39 – 1,98 gr dapat dilakukan pada Pen-culture dengan menggunakan penutup. Hal ini dikarenakan presentase kelangsungan hidup anakan teripang pasir yang didederkan pada Pen-culture sebesar 84 – 86,67 % dengan rata-rata persentase kelangsungan hidup 85,33 % dan kisaran pertumbuhan berat tubuh sebesar 2,54 – 12, 97 gr dengan rara-rata pertumbuhan mutlak berat tubuh sebesar 6,77 gr. Kata kunci : Pendederan, Teripang pasir, Pen-culture